The Influence of Word Choice (Diction) on Covid-19 Vaccination Campaign News on the Psychological Condition of Readers - Aztiana Aztiana; Fitriani Fitriani; Nur Hikmah; Muhammad Fadhil Marwan; Muhammad Irfan; Mantasiah R. (INSIGHT: Indonesian Journal Social Studies and Humanities, 2021)
This study aims to find out how the diction in the news regarding the vaccination campaign Covid-19 reported on various news portals online affects the perception and psychological condition of the readers by analyse the content of the news using a qualitative approach to the method of discourse analysis and critical discourse analysis of the Teun A. Van Dijk model. The data in this study are qualitative data in the form of word selection (diction) from the news of the covid-19 vaccination campaign which is the result of discourse analysis and qualitative descriptive data from reader responses from interviews. The results of this study are that there are several outlines of topics that often appear in the news of Covid-19 vaccinations. But the most dominant is the news that emphasizes the quality and effectiveness of the vaccine. In addition, in the 2 news titles that have been analysed for diction, there is a tendency to use words that tend to be positive, such as effective, superior, drastic, prevent, reduce, protect, prove, and save lives. Furthermore, it also uses words that have scientific meaning such as research, clinical trials, and studies. Then tend to use words that sound scary like death, serious condition, serious illness, and so on. In addition, the two news reports state the effectiveness of the vaccine by using a percentage of numbers, and finally make relevant research results as a benchmark for the validity of the news as well as a reinforcement for news when it is read by readers. Based on the results of interviews from the respondents and the interpretation of the data above, it can be concluded that the diction in the news regarding the Covid-19 vaccination does not have a significant influence on the psychological condition of some readers.Keywords: Diction, Word Choice, Psychological Condition, Vaccination Campaign News